The impact of flipped classroom on English proficiency of first-year Chinese urban and rural pre-service teachers - Chen, Wei (Frontiers in Psychology, 2024)
Introduction In recent years, China has made strides in adopting student-oriented teaching approaches, particularly in tertiary English education, through the integration of enhanced technology. This study aimed to investigate the impact of flipped classroom on the English proficiency of first-year pre-service teachers at a Chinese normal university. It also sought to determine whether educational background (urban or rural) interacted with the teaching approach (flipped or traditional) in affecting the language proficiency of the learners. Methods A quasi-experimental design was utilized with two treatments: a flipped classroom approach and a traditional teacher-centered teaching approach. Both approaches were implemented in the Integrated English Course over a 12-week semester. Two randomly selected classes, consisting of 60 pre-service teachers in each class, were assigned to either the experimental or control group. Data were collected from pretest and post-test assessments and analyzed using two-way ANOVA. Results The results revealed a positive impact of the flipped classroom and a significant interaction between educational background and teaching approach on English proficiency. Specifically, urban pre-service teachers achieved higher English proficiency than their rural peers when taught in the flipped classroom, but not in the traditional classroom. Furthermore, urban pre-service teachers in the flipped classroom outperformed their urban peers in the traditional classroom, while rural pre-service teachers did not show any significant difference in their performance between the two classes. Discussion The findings suggested that the flipped classroom approach was more effective than the traditional approach for Chinese pre-service teachers, particularly those with an urban educational background. However, it is important to ensure that rural learners receive sufficient support to benefit equally from this innovative teaching approach. Accordingly, implications and recommendations for future research are discussed.